« The reality is, Mr. Speaker, that… » : de la modalité au positionnement énonciatif dans les structures projectives - Florine Berthe (Anglophonia)
We focus on the notion of stance-taking and in the areas of discourse where it manifests itself within the genre of parliamentary debate. This article deals with a family of structures that can be found in spoken English and which look like bi-clausal structures made up of two parts connected by a form of the copula be. We include in our research structures such as the thing is as well as other variants such as the point is, the fact is, the funny thing about this is or the point I want to make is. All these structures are generally studied for their projective and focalizing functions as well as their discourse-pragmatic functions. These structures are said to be a way for the speaker to comment upon the discourse that follows, which often contains the whole propositional content of the utterance and correspond to the rheme. In the particular parliamentary debate under study, these structures are strategically used by the different speakers to mark a stance. Drawing on previous research, we will present the general characteristics of these structures which make them ideal places where we can find stance markers. Regarding stancetaking, we will show that these structures can operate in two ways. Firstly, some variants resort to nouns which have a modal meaning. In that case, the projective structure is used by the speaker to express a modal stance on the rheme. Secondly, these structures can be used to underline whose stance is expressed in the second part of the bi-clausal structure. When the stance is attributed to a third person, the speaker usually indicates whether or not they adhere to this content.